To be full of oneself: performance destruction in Shakespeare's Hamlet & Julius Caesar - Ho, Ching Wai (Nanyang Technological University, 2023)
Many of Shakespeare’s characters are often subjected to certain roles or personalities either by themselves or by others, sometimes playing the role of disguise with specific purposes. By presenting conflict, trauma and madness through soliloquies, the literal act of acting, and literal and symbolic death, the distinction between the public and the private self is blurred in Shakespeare's Hamlet and Julius Caesar. Shakespeare’s plays therefore problematises the act of performance as it not only complicates the relationship between the public and the private, it destroys this dichotomy. Performance, therefore, as the essay title announces, acts as a constriction, more like a chaotic and careless and thereby dangerous freedom.